Exploring Wells-Dawson Clusters Associated With the Small Ribosomal Subunit - Crans, Debbie C.; Sánchez-Lombardo, Irma; McLauchlan, Craig C. (Frontiers in Chemistry, 2019)
The polyoxometalate W18P2O626–, the Wells-Dawson cluster, stabilized the ribosome sufficiently for the crystallographers to solve the phase problem and improve the structural resolution. In the following we characterize the interaction of the Wells-Dawson cluster with the ribosome small subunit. There are 14 different W18P2O626– clusters interacting with the ribosome, and the types of interactions range from one simple residue interaction to complex association of multiple sites including backbone interactions with a Wells-Dawson cluster. Although well-documented that bridging oxygen atoms are the main basic sites on other polyoxometalate interaction with most proteins reported, the W=O groups are the main sites of the Wells-Dawson cluster interacting with the ribosome. Furthermore, the peptide chain backbone on the ribosome host constitutes the main sites that associate with the Wells-Dawson cluster. In this work we investigate the potential of one representative pair of closely-located Wells-Dawson clusters being a genuine Double Dawson cluster. We found that the Double Dawson structure on the ribosome is geometrically sound and in line with other Double Dawson clusters previously observed in the solid state and solution. This information suggests that the Double Dawson structure on the ribosome is real and contribute to characterization of this particular structure of the ribosome.